MEDICAL AND SOCIAL APPROACHES TO ENSURE EARLY DIAGNOSIS AND PREVENTION OF ALLERGIC RHINITIS AT THE REGIONAL LEVEL - P.V. BEREZHANSKIY; A.V. FADEEV; L.B. SHUBIN (Паёми Сино, 2022)
Objective: To evaluate the effectiveness of a screening programme for detecting allergic rhinitis (AR) and its risk factors (RFs) based on a 5-year epidemiological analysis among children ages 0 to 17 years in the Odintsovo urban district in Moscow Oblast, Russia.